Nutrition science, marketing nutrition, health claims, and public policy - Ghosh, Dilip K.; Bogueva, Diana, 1974-; Smarta, R. B., 1944- (Academic Press, an imprint of Elsevier, 2023)
Nutrition Science, Marketing Nutrition, Health Claims, and Public Policy explains strategies to guide consumers toward making informed food purchases. The book begins with coverage of nutrition science before moving into nutrition marketing, social marketing and responsibility, consumer perception and insight, public health policy and regulation, case studies, and coverage on how to integrate holistic health into mainstream brand marketing. Intended for food and nutrition scientists who work in marketing, manufacturing, packaging, as well as clinical nutritionists, health care policymakers, and graduate and post graduate students in nutrition and business-related studies, this book will be a welcomed resource. Includes case studies, points-of-view, literature reviews, recent developments, data and methods Explores intrinsic and extrinsic motivators for consumer purchasing behaviors Covers each aspect of "Seed to Patient" pathway.--Provided by publisher.